Evaluación del efecto de la solución AgCelence de BASF para control de enfermedades foliares fúngicas en el cultivo de maíz. - Estrada Miguez, Jheferson Estalin (2021)
Since corn is one of the most consumed and economically important agricultural products in the country, it is necessary to implement new models to increase production, search for new agrochemical technologies and thus meet the food needs. Therefore, the objective of this research was to evaluate BASF's AgCelence portfolio in comparison to other portfolios commonly used by producers in the area. For this purpose, an experimental corn plot was established at the "La María" Campus of UTEQ, located in the Mocache canton, province of Los Ríos. For the evaluation of the treatments in the field, a completely randomized block design (CRBD) was implemented, composed of four treatments and four replications (one experimental unit per replication). Regarding the results, the treatments presented statistically different averages in most of the variables studied. However, with respect to agronomic characteristics, it was possible to observe a parity in the averages obtained by the treatments in the variable stem diameter, the opposite case occurred in the variable plant height (m) where the advantage of T3 (Technology 3) with 1.91 m was visible. Within productive parameters such as: ear length (cm), ear diameter (cm), weight of 100 seeds (g) and grain yield (mt/ha), T1 (Technology 1) stood out with 18.16 cm, 4.73 cm, 42.00 g and 11.20 mt/ha respectively, except for the variable number of ear rows where no statistical differences were identified. On the other hand, there was also a poor presence of diseases and absence of visible disease in each of the treatments, including the control. Finally, the treatment with the best profitability was T1, corresponding to the AgCelence solution, with 38.76% more than the control. Keywords: Zea mays, plant health, portfolio, FRAC, resistance